Innovation Hub: Media Kolaborasi Menuju Pemerintahan Daerah Inovatif - Herie Saksono (Nakhoda: Jurnal Ilmu Pemerintahan, 2020)
The digital age is demanding local governments to become more innovative in their governance. Innovation is a necessity in the formulation of policies to be more qualified and implementative, service provision becomes more excellent, ultimate and optimal, accelerating public welfare, increasing investment, and creating regional independence in order to have excellence and competitiveness. The problem is, based on empirical facts there are still many local governments (LGs) that cannot be categorized as innovative LGs. What is the right strategy to change it so that local governments are more innovative? This study is an observation during the facilitation of regional innovation activities. The goal is to find solutions while simultaneously driving massive change. The method used is qualitative with descriptive-comparative analysis. Data collection is done by triangulation, while data analysis is inductive. Innovation hub (i-hub) is a solution that functions as a medium of collaboration between innovation actors, the Government, regional governments, as well as village governments, communities, and development stakeholders in the regions. Through the innovation hub, it is expected that an innovation spectrum will be held that includes leadership innovation, administrative innovation, management innovation, policy innovation, social innovation, technological innovation, and innovation disruption. In general, it can be emphasized that the innovation hub is a collaborative media that is able to shape the innovation ecosystem, accelerate innovation, create innovators, and build dynamic and sustainable local government. In due time, the innovation hub triggers innovation and changes in local government to become more dynamic, creative, adaptive, innovative, productive, futuristic, and prospective. It is recommended that each local government change immediately, encourage the institutionalization of i-hub, and manage it collaboratively to foster regional innovation.